Empirical Analysis of Destination Image Through Tiktok Video Comments - Sobarna, Aditia (Journal of Tourism Sustainability, 2023)
This study examines the role of comments on the TikTok social media platform in shaping the image of tourist destinations, focusing on Borobudur Temple, a world heritage site in Indonesia. A thematic analysis of comments on TikTok reveals the public's perception of Borobudur Temple as a historical destination enriched with spiritual values and myths. Terms such as "myth" and "belief" predominate, highlighting the temple's uniqueness and religious backdrop. Social media, particularly TikTok, plays a crucial role in shaping these perceptions. By understanding and addressing these perceptions, marketing strategies on digital platforms can be more effective, enhancing the global appeal of Borobudur Temple. The overall findings underscore the power of social media in shaping the image of tourist destinations and provide recommendations for stakeholders in the tourism industry.